Islamic spiritual guidance as a solution to the problem of spiritual well-being - Nihayah, Ulin; Manggarani, Mustika; Mintarsih, Widayat; Kibtiyah, Maryatul (Journal of Advanced Guidance and Counseling, 2024)
Purpose - The purpose of this study was to examine the implementation of Islamic spiritual guidance as a solution to the spiritual well-being problems faced by diabetes mellitus patients at PKU Muhammadiyah Gubug Hospital. This research focuses on the impact of holistic care involving physical, psychological, psychosocial, and spiritual dimensions.Method - This study employed a qualitative descriptive approach with a phenomenological perspective. Data collection methods included observation, in-depth interviews, and documentation. Participants consisted of patients and their families, along with Islamic spiritual counsellors at PKU Muhammadiyah Gubug Hospital.Result - The results showed that Islamic spiritual guidance is delivered through verbal methods (counselling, advice, and motivation), written or visual methods (Islamic-themed writings and artwork displayed in hospital rooms), and audio methods (recitation of Qur'anic verses via speakers). The guidance materials included teachings on tawakal (reliance on God), tauhid (monotheism), and worship practices (prayer and purification methods adapted for patient conditions). The study found that these methods enhanced patients' personal and communal well-being, helped them find purpose in life, and fostered positive attitudes.Implication - This method suggests that integrating Islamic spiritual guidance in healthcare settings can significantly improve the spiritual well-being of patients, enhancing their overall recovery process and quality of life.Originality - This research is the first study to comprehensively explore the integration of Islamic spiritual guidance as a holistic approach to address the spiritual well-being of diabetes mellitus patients in a hospital setting, particularly at PKU Muhammadiyah Gubug Hospital.***Tujuan - Penelitian ini bertujuan untuk mengetahui implementasi bimbingan rohani Islam sebagai solusi terhadap masalah kesejahteraan spiritual pada pasien diabetes melitus di Rumah Sakit PKU Muhammadiyah Gubug. Fokus penelitian ini adalah dampak dari pelayanan holistik yang meliputi dimensi fisik, psikologis, psikososial, dan spiritual.Metode - Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan perspektif fenomenologi. Teknik pengumpulan data yang digunakan adalah observasi, wawancara mendalam, dan dokumentasi. Partisipan terdiri dari pasien dan keluarga pasien, serta petugas rohani di Rumah Sakit PKU Muhammadiyah Gubug.Hasil - Hasil penelitian menunjukkan bahwa bimbingan rohani Islam dilakukan melalui metode lisan (konseling, nasihat, dan motivasi), metode tertulis atau visual (menempatkan tulisan dan karya seni Islami di kamar rumah sakit), dan metode audio (melantunkan ayat-ayat suci Al Qur'an melalui pengeras suara). Materi bimbingan meliputi ajaran tawakal (berserah diri kepada Allah), tauhid (keimanan kepada Allah), serta bimbingan ibadah (salat dan thaharah yang disesuaikan dengan kondisi pasien). Studi ini menemukan bahwa metode ini mampu meningkatkan kesejahteraan pribadi dan komunal pasien, membantu mereka menemukan tujuan hidup, dan mendorong sikap positif.Implikasi - Metode ini menunjukkan bahwa integrasi bimbingan spiritual Islam dalam perawatan kesehatan dapat secara signifikan meningkatkan kesejahteraan spiritual pasien, sehingga mempercepat proses pemulihan dan meningkatkan kualitas hidup mereka.Keaslian - Penelitian ini merupakan penelitian pertama yang secara komprehensif mengeksplorasi integrasi bimbingan rohani Islam sebagai pendekatan holistik dalam menangani kesejahteraan spiritual pasien diabetes melitus di rumah sakit, khususnya di Rumah Sakit PKU Muhammadiyah Gubug.